Molecular and Cellular Characterization of Synovial Joint Tissues: Insights into Subsynovial Adipose Tissue, Cell-Type Heterogeneity, and Osteoarthritis - Tilouche, Bahaeddine (Université d'Ottawa | University of Ottawa, 2026)
Osteoarthritis (OA) is a chronic degenerative joint disease that affects nearly 15% of Canadians, with an estimated healthcare cost exceeding $11 billion annually by 2031. Current regenerative strategies primarily focus on mesenchymal stem cells (MSCs); however, the precise identity of joint-resident stem cells and their responses to physiological changes remain poorly understood. This thesis addresses this gap through a multi-level investigation of joint tissues in human and animal models. First, we examined surgical samples of human sub-synovial adipose tissue (ssAT) of the hip to distinguish cellular and molecular changes associated with OA from those of normal aging. Using immunohistochemistry and targeted transcriptomics, we demonstrated that OA is characterized by increased mesenchymal stem/progenitor cell content, vascular remodeling, and immune dysregulation, in contrast to the more subtle changes associated with normal aging. To further characterize joint tissue heterogeneity, we generated a comprehensive single-cell atlas of the murine postnatal joint by integrating publicly available single-cell datasets with a spatial transcriptomics dataset produced in this work. This atlas highlights the distinct cellular populations and transcriptional programs underlying joint maintenance and disease susceptibility. Building on these insights, we identified Tbx18 as a putative marker of joint-resident cells and performed lineage tracing combined with three-dimensional (3D) confocal imaging in mice. We show that Tbx18⁺ cells populate the synovium, meniscus, articular cartilage, and tendons, where they remain quiescent under homeostasis but become activated following injury. Collectively, this work highlights the ssAT as an active contributor to OA pathogenesis, establishes the first integrated atlas of the postnatal joint, and identifies Tbx18 as a powerful surrogate marker for studying all tissues in the joints. These findings provide new insights into the biology of joint tissues and lay the groundwork for stem cell–based regenerative strategies in orthopedic disease.
Keywords: Osteoarthritis; Synovial joints; Subsynovial adipose tissue; Aging; Spatial transcriptomics; Joint atlas; Stem cells; Mesenchymal progenitors; Vasculature; Stem cell niche; Hip; Knee